Diversidade de fungos micorrízicos em diferentes sistemas de manejo do solo no Bioma Cerrado, MS - SOUZA OLIVEIRA, Anderson; COÊLHO, Roseline da Silva; SCHIAVO, Jolimar Antonio (ANAIS DO ENIC, 2024)
-